Perancangan Ulang UI/UX Website Sistem Informasi Akademik Pada Universitas XYZ Menggunakan Metode Lean UX - Fahreo Iddo Putera Dewangga; Prisa Marga Kusumantara; Dhian Satria Yudha Kartika (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
Based on the resulSSR of interviews with 14 active users of SIAMIK from XYZ, issues related to the user interface (UI) and user experience (UX) of SIAMIK were identified. The purpose of this research is to design the UI/UX of the SIAMIK website using the Lean UX method, aiming to achieve improved usability. This study will discuss the redesign of the SIAMIK UI/UX using the Lean UX method, which is user-centered and incorporates Lean and Agile principles to minimize resource waste and create a user-oriented product. The design evaluation phase will be conducted using three usability aspecSSR. The test resulSSR yielded an Effectiveness score of 97.0%, an Efficiency score of 97.0%, and a SUS (System Usability Scale) score of 83.50.